ANALISIS PREDIKSI KEBANGKRUTAN PERUSAHAAN DENGAN PENDEKATAN Z-SCORE ALTMAN PERUSAHAAN SUB-SEKTOR TEKSTIL YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2019-2021: indonesia - Indana Julfa Baliang; Fauziyah Lamaya (Jurnal Akuntansi Universitas Muhammadiyah Kupang, 2023)
The textile and garment industry in Indonesia has become one of the backbones of the manufacturing sector in recent decades. The textile and garment industry contributes significantly to economic growth, creating considerable employment, this industry is also export-oriented and also encourages an increase in domestic and foreign investment. This study aims to determine the Analysis of Company Bankruptcy Prediction with Altman's Z-Score Approach in Sub-Se Companies In textile sub-sector companies listed on the Indonesia Stock Exchange for the 2019-2021 period. The research method used is a quantitative descriptive method, using Altman's Z-Score approach. The sample in this study is textile sub-sector companies listed on the Indonesia Stock Exchange in 2019-2021 consisting of 9 companies. The source of data in this study is secondary data, namely in the form of financial statement data published by textile companies published by the Indonesia Stock Exchange and obtained from internet media by downloading through the website: www.idx.com. The results showed that the calculation results of 9 textile sub-sector companies Analysis of Textile companies with the Altman model showed that Analysis of Textile companies with the Altman model showed 1 company that had the potential to experience "bankruptcy" (distress) in the 2019 analysis year. 3 companies in the 2020 analysis year. And 2 companies in the 2021 analysis year. Companies that fall into the category of "prone to bankruptcy" (gray area) as many as 5 companies in the year of analysis 2020. And 2 companies in the 2021 analysis year. Companies that are categorized as "prone to bankruptcy" (gray area) as many as 5 companies in the 2019 analysis. 3 companies of the year of analysis 2020. And 4 companies in the 2021 analysis year. Companies that are included in the category of not bankrupt or healthy as many as 3 companies that are included in the healthy category in the 2019 analysis year. 3 companies in the 2020 analysis year. And 3 companies in the 2021 analysis year.